Coal fracturing under dynamic load induced by methane deflagration - Ting Liu; Jiabin Hu; Yu Wang; Cheng Zhai; Jianfeng Li; Xiangguo Kong; Zhongqiu Liang (International Journal of Coal Science & Technology)
Abstract To elucidate the dynamic characteristics of in-situ methane deflagration in coalbed methane wellbores and its mechanisms for fracturing coal rock, this study first developed a simulation experimental system specifically designed for methane in-situ deflagration fracturing. This experimental system, which is capable of withstanding pressures up to 150 MPa and meanwhile applying axial and confining pressures of up to 50 MPa to rock cores, enables the coupled simulation on methane deflagration and rock core fracturing processes. With the aid of this experimental system, physical simulation experiments on in-situ methane deflagration fracturing were conducted, and the following findings were obtained. Methane deflagration loads in enclosed wellbores exhibit characteristics of multi-level pulsed oscillation. With the rise of initial gas pressure, the peak deflagration load increases approximately linearly, with the pressure amplification factor spanning from 23.14 to 31.10, and its peak loading rate grows exponentially. Accordingly, the fracture volume and fracture porosity augment. To be specific, when the initial gas pressure rises from 0.6 to 2.4 MPa, the fracture volume and fracture porosity augment by factors of 14.0 and 8.73, respectively. The fractal dimension of spatial distribution of fractures also increases with the rise of deflagration load, indicating that a higher deflagration load conduces to the development of a larger and more complex fracture network. Methane deflagration fracturing is characterized as a composite fracture mode that involves the impact of strong stress waves and the driving force of high-pressure fluids. The primary factors influencing damage to coal-rock include the high-stress impact in the initial stage of deflagration, the fluid pressure driving effect in the middle stage, and the thermal shock resulting from high temperatures in the later stage.